2019
DOI: 10.1002/jia2.25225
|View full text |Cite
|
Sign up to set email alerts
|

Beyond HIV prevention: everyday life priorities and demand for PrEP among Ugandan HIV serodiscordant couples

Abstract: IntroductionPre‐exposure prophylaxis (PrEP) to prevent HIV infection is being rolled out in Africa. The uptake of PrEP to date has varied across populations and locations. We seek to understand the drivers of demand for PrEP through analysis of qualitative data collected in conjunction with a PrEP demonstration project involving East African HIV serodiscordant couples. Our goal was to inform demand creation by understanding what PrEP means – beyond HIV prevention – for the lives of users.MethodsThe Partners De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 31 publications
1
29
0
Order By: Relevance
“…In this regard, PLHIV and their sexual partnerships should receive counseling and education with serodifferent couples about these HIV prevention options in isolation or their association with other risk management and prevention methods such as PrEP and condoms ( 48 ) .…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, PLHIV and their sexual partnerships should receive counseling and education with serodifferent couples about these HIV prevention options in isolation or their association with other risk management and prevention methods such as PrEP and condoms ( 48 ) .…”
Section: Discussionmentioning
confidence: 99%
“…While PrEP is nearly 100% effective at preventing HIV infection when adherence is high, the counseling delivered with PrEP in the Partners Demonstration Project still emphasized the importance of continued condom use to prevent pregnancy, STIs, and as a backup for HIV prevention [23,24]. HIV serodiscordant couples have reported the use of condoms as a barrier to establishing intimacy and closeness within the relationship [15,16,20]. Thus, counseling on continued condom use for HIV prevention with the delivery of PrEP may be a missed opportunity to help HIV serodiscordant couples re-establish intimacy in their relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, these couples reported that condom use works against re-establishing intimacy and closeness, further elongating their emotional distance [15,16,18]. Second, many couples report the desire for children and PrEP provides an opportunity to practice safer conception to minimize transmission risk between them [15,17,19,20]. There is also evidence, however, that following PrEP initiation sexual behaviors associated with HIV risk may not change within HIV serodiscordant couples for reasons including inconsistent PrEP adherence-patterns that are often established early after initiation [5,21], lack of trust in the protective effects of PrEP for HIV prevention [16], and complex partner dynamics surrounding the negotiation of sex and condom use [20,22].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations